Health-related quality of life among older citizens in Bangladesh - Abdur Razzaque Sarker (Elsevier, 2021)
Despite improvements in many health indicators in the last few decades, providing access to affordable health care for elderly people is a major challenge in low- and middle-income countries like Bangladesh. The objective of this study was to measure the health-related quality of life (HRQoL) among older citizens in Bangladesh and to determine the factors influencing HRQoL. A cross-sectional household survey was conducted in the Tangail district of Bangladesh. The study was conducted among elderly citizens (aged 60 years or above, according to the National Policy on Elderly People in Bangladesh). Logistic and multiple regression models were used to identify the potential factors affecting the HRQoL of older citizens. A total of 585 older citizens participated in the study. The mean EQ-5D and VAS scores were 0.51 and 0.55, respectively. Most of the older citizens suffered from anxiety or depression (81.6%), followed by pain or discomfort (81.4%). The HRQoL is significantly higher for male than female older citizens (P<0.001). The older citizens currently involved in day labour or business had significantly less health-related problems in the mobility (p ​< ​0.001) and self-care (p ​< ​0.01). Housewives were 2.17 times more likely to report health problems in the 'anxiety or depression' while less likely to suffer 'usual activities' related health problems (p ​< ​0.001). It is recommended that health authorities and relevant stakeholders prioritize various programs promoting health among the elderly, such as health education, health promotion and health resources, in order to improve HRQoL among the elderly citizens in Bangladesh.